2004
DOI: 10.1002/path.1503
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant CpG island hypermethylation of multiple genes in prostate cancer and prostatic intraepithelial neoplasia

Abstract: To date, several reports have been published about CpG island methylation of various genes in prostate cancer. However, most of these studies have focused on cancer tissue only or a single gene and data about concurrent methylation of multiple genes in prostate cancer or prostatic intraepithelial neoplasia (PIN) are limited. The aim of the present study was to determine the methylation profile of 11 tumour-related genes in prostate cancer and PIN. Seventy-one samples, including 37 prostate cancers, 14 PINs, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
226
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 219 publications
(244 citation statements)
references
References 25 publications
14
226
4
Order By: Relevance
“…Our data included paired tumor, nontumor tissues, and plasma samples from cases, which allowed us to investigate not only tumor/nontumor differences, but also the tissue-plasma correlations. The frequency of hypermethylation in PCa tissues for GSTP1, p16 (CDKN4A), and APC ranged from 83.3% to 95.8%, similar to previous studies, although different approaches were used for methylation detection ( Jeronimo et al, 2004;Kang et al, 2004;Maruyama et al, 2002). Consistent with previous research ( Jarrard et al, 1997;Chu et al, 2002;Kang et al, 2004;Chuang et al, 2007;Phe et al, 2010), we also found significant tumor/nontumor differences in gene-specific methylation levels (Fig.…”
Section: Discussionsupporting
confidence: 54%
“…Our data included paired tumor, nontumor tissues, and plasma samples from cases, which allowed us to investigate not only tumor/nontumor differences, but also the tissue-plasma correlations. The frequency of hypermethylation in PCa tissues for GSTP1, p16 (CDKN4A), and APC ranged from 83.3% to 95.8%, similar to previous studies, although different approaches were used for methylation detection ( Jeronimo et al, 2004;Kang et al, 2004;Maruyama et al, 2002). Consistent with previous research ( Jarrard et al, 1997;Chu et al, 2002;Kang et al, 2004;Chuang et al, 2007;Phe et al, 2010), we also found significant tumor/nontumor differences in gene-specific methylation levels (Fig.…”
Section: Discussionsupporting
confidence: 54%
“…This implies that hypermethylation of IGFBP3 occurs as an early event in prostate carcinogenesis and supports a clonal relation between the tumour and HGPIN lesion. We also found methylation of GSTP1 in a high frequency of HGPIN foci, consistent with previous reports (Nakayama et al, 2003;Kang et al, 2004).…”
Section: Discussionsupporting
confidence: 93%
“…RUNX3 was also identified as one of the five most informative genes of the CpG island methylator phenotype of colorectal cancer (Weisenberger et al, 2006). In addition to gastric and colon cancer, RUNX3 is frequently inactivated in cancers of the lung, bladder, pancreas, liver, prostate, bile duct, breast, larynx, esophagus, and testicular yolk sac by either DNA hypermethylation or mislocalization of the protein in the cytoplasm (Kato et al, 2003;Goel et al, 2004;Kang et al, 2004;Li et al, 2004;Tozawa et al, 2004;Xiao and Liu, 2004;Ito et al, 2005;Kim et al, 2005b;Lau et al, 2006). Among the lung cancers, RUNX3 promoter hypermethylation is preferentially found in lung adenocarcinomas (Sato et al, 2006).…”
Section: Introductionmentioning
confidence: 99%